(untitled) (Journal of Applied Learning and Teaching, 2022)
This non-systematic review explores the state of public primary school teachers in Sub-Saharan Africa (SSA), including pre-service training, professional development, absenteeism and teaching and learning materials (TLMs). Overall, there are severe deficits in teacher content knowledge, pre- and in-service training, quality and quantity of available teaching and learning materials, and attendance. However, cases of resilience and effectiveness are also reported, based on qualitative data, which is also used to discuss decentralization and bottom-up approaches to educational challenges in resource-poor settings.